ALIH TUTUR BAHASA INGGRIS DALAM OXFORD ENGLISH DAILY CONVERSATION - I Gusti Ayu Agung Sintha Satwika (Universitas Warmadewa, 2018)
[Title: Turn-Taking in English found in Oxford English Daily Conversation] This research aims at investigating and analyzing the turn-taking in English conversation. The data of this writing were collected from a video entitled Oxford English Daily Conversation. This study was conducted by applying the qualitative method of which the discussion was presented descriptively. The data of this study were obtained by using observation and note taking technique. The result of this study indicates that turn-taking in English conversation can be signaled by intonation, stress of word, and pause. Those signals indicate whether the speaker is taking, holding, or yielding the conversation floor.